A Comparative Study of Social Entrepreneurship Contribution to the Territory's Sustainable Development - Marwane El Halaissi; Oualid Benalla; Santi Rahmawati (Journal of Social Entrepreneurship Theory and Practice, 2024)
Understanding the importance of exploring the dynamics of social entrepreneurship (SE) is crucial as it has the power to create positive changes in society, the economy, and the environment, ultimately leading to a fairer and more sustainable global community The purpose of this paper is to explore and elucidate SE's multifaceted input into propelling knowledge of sustainable development and its contribution to the territory's sustainable development. Data was gathered over a two-year period through field research that comprised interviews and secondary sources (field notes and internal documents). A multiple comparative case study was used. This perspective allows us to emphasize the role of SE in the activities related to implementing the philosophy of sustainable development and the considerable contribution of its action to the achievement of the various objectives that the state has set itself in its fight against the social, economic, and environmental challenges affecting the territory. The data collected illustrates the input or contribution of SE to the sustainable development of the territory by creating multiple added values at the local level. Furthermore, by adopting a territorial view based on the many processes carried out by SE, this research provides an alternate reading of the results of SE action, connecting them to the numerous concerns of sustainable development.